Tungsten inert gas surface modification of SAE 4140 steel - Eroglu, M; Önalp, S (Sage Publications Inc, 2002)
In the present study, the surface of SAE 4140 steel was separately are melted and alloyed with preplaced high carbon ferrochromium powder using a. tungsten inert gas (TIG) arc heat source. The effects of specimen thickness and heat input for arc melting and thickness of preplaced high carbon ferrochromium powder layer for surface alloying on the microstructure, hardness and wear properties of the modified surfaces were investigated. Following arc melting and surface alloying, conventional characterisation techniques such as optical microscopy, scanning electron microscopy (SEM), energy dispersive spectrography (EDS) and X-ray diffraction were employed to study the microstructure of the arc melted and alloyed surfaces. Hardness measurements were performed across the modified zones and wear properties of the surfaces were evaluated by a pin-on-disc abrasive wear testing method. The results indicated a significant increase in surface hardness after melting at low heat input (0(.)7 kJ mm(-1)) and alloying with a preplaced high carbon ferrochromium powder layer giving a surface composition of 3%C and 25(.)8%Cr, with higher wear resistance surfaces. This was attributed to the fully martensitic microstructure for surface melting and the high volume friction of Cr7C3 carbides in the matrix of austenite for surface alloying.
Keywords: Abrasion Resistance; Wear Behavior; Fracture-Toughness; Laser Irradiation; Stainless-Steel; Cast-Iron; Titanium; Chromium; Microstructure; Alloys